THE EFFECT OF ENDORPHINE MASSAGE AND GINGER AROMATHERAPY ON DECREASING LOW BACK PAIN INTENSITY IN WORKING PREGNANT WOMEN - Magdalena Agu Yosali; Ratih Suryaman; Salsalina Yuniarti Ginting; Yuliana Yuliana; Emilya Irawan; Ranti Ranti (Jurnal Keperawatan Respati Yogyakarta, 2022)
This study aims was to determine the effect of endorphine massage and ginger aromatherapy on decreasing the intensity of low back pain in pregnant women who work. This type of research is a Quasy experimental design using a two group pre and posttest design with a control group. The sampling technique in this study was proportional random sampling, so the number of respondents needed in this study were 24 respondents of TM III pregnant women for each intervention group and control group, so the total number of respondents was 24 respondents. Data analysis using Simple Paired t-test. Before giving endorphin massage using ginger aromatherapy on the decrease in the intensity of low back pain in pregnant women who work in the intervention group of 12 respondents there were 5 respondents with moderate pain levels (41.6 %), and the control group of 12 respondents there were 6 with pain levels mild (50%). The effect of after giving endorphin massage using ginger aromatherapy on the decrease in the intensity of low back pain in pregnant women who work in the intervention group of 12 respondents there are 6 respondents who do not feel pain (40%), and the control group of 12 respondents there are 6 with moderate pain levels ( 40%). Asymp.sig (2 tailed) is worth 0.000, which means <0.05. Then it can be concluded that "Ha Accepted". Endorphins massage using ginger aromatherapy is effective to reduce the intensity of low back pain in pregnant women